KODE ETIK ASN DALAM MENJAGA NETRALITAS PADA PEMILIHAN PRESIDEN 2024 - Rini Admiwati; Istiana Hermawati (HUMANITIS: Jurnal Homaniora, Sosial dan Bisnis, 2024)
The 2024 Presidential Election has indeed ended, but the hypocritical atmosphere is still very pronounced and colorful. There are many pros and cons going on. Starting from the Constitutional Court which is considered unethical, there are many issues regarding sara and many more. Many people contributed to the election process. ASN as a state civil servant does not escape attention, considering that ASN is regulated by Law Number 5 of 2014 or better known as the ASN Law, which is a law that regulates all matters regarding the State Civil Apparatus (ASN). This law is a regulatory framework to encourage the creation of ASN consisting of Civil Servants (PNS) and Government Employees with Work Agreements (PPPK) who have integrity, are professional, neutral and free from political interference. The research approach used in this research is qualitative with a literature study research method (Putrihapsari & Fauziah, 2020). Literature study is research carried out by reviewing various literature studies required in research (Nazir, 2014), by utilizing literature to obtain data in the field without the need to go directly to informants or the community. Through this research, it is hoped that ASN will be able to implement a code of ethics that regulates moral principles that are taken into consideration in making decisions and a code of behavior that regulates what must be done, what can be done and what cannot be done. Compliance with the code of ethics will form very important behavior in creating professional ASN employees because professionalism is not only related to having competence but also attitudes and behavior in carrying out their duties.